Flexing Phenomena of Ritual Piety in Social Media and The Loss of Empathy Among The Muslims (Proceeding of Dakwah Saizu International Conference, 2023)
This research is a descriptive qualitative research using a phenomenological approach. This study aims to describe the phenomenon of religious flexing and the loss of a culture of empathy among Muslims. Data collection techniques are carried out by collecting documents in the form of uploads in the form of pictures, photos or videos from social media YouTube, Instagram and Facebook. This data is then analyzed with the support of secondary sources in the form of data relevant to this research. The data was obtained from books, journals, and websites. The phenomenon of flexing is included in the theory of structural functionalism, flexing becomes a new culture and becomes a spectacle that has sprung up among the public. Social media such as Instagram and Facebook, YouTube with content that is the talk of all levels of society. Displaying piety on social media is a matter of ritual worship. With the aim of getting appreciation, honor and social status.